Parent/Guardian Experiences With the Healthcare System and Community Supports for Pediatric Asthma Management. (April 2022) - Rolke, Laura J; Griffin, Sarah F; Hamilton, Joel; Mayo, Rachel; Williams, Joel E; Rennert, Lior; Sease, Kerry K
Determinants of pediatric asthma management include child, family, healthcare, and community factors. The purpose of this study is to investigate how parents/guardians are impacted by and act on these factors to aid in their child's asthma self-management. Interviews were conducted in Fall 2020 with 12 female parents/guardians of Black/African American children who participated in a community paramedic pilot study with their child in South Carolina. Children in the initial study had an asthma diagnosis of moderate persistent asthma, had Medicaid insurance, and were determined high-risk for emergency room presentation. Inductive and deductive qualitative analysis identified that child management self-efficacy and independence, parent/guardian health literacy, parent and child negative experiences related to asthma diagnosis and management, asthma management tools, and social support from multiple sources impact child self-management. Findings from this study highlight the importance of clear asthma education and management tool recommendations from healthcare and community providers, particularly for parents/guardians with low health literacy. Health literacy impacted parental responses and likely how families comprehend Medicaid and clinical asthma guidance.